Chronicling the Experiences of Mathematics Learners and Teachers on the Usage of Guided Discovery Learning (GDL) in Enhancing Learners’ Academic Performance - Mabhoza, Zizipho; Olawale, Babawande Emmanuel (Research in Social Sciences and Technology, 2024)
South Africa has been battling with the poor performance of learners in Mathematics for a long time, with the Eastern Cape province being the worst-performing province. The Department of Education and other educational stakeholders have embarked on a journey of searching for solutions. Some of these include the use of Information communication technologies (ICT), code switching, intervention programs (IP) and the use of different learners centered approach to teach Mathematics, to mention a few. Hence, this present study investigated how the guided discovery learning strategy can be used to enhance the performance of Grade 10 learners in Amathole West district, Eastern Cape Province, South Africa. Underpinned by an interpretivist paradigm and qualitative research approach, the study employed a participatory action research. A convenient sampling technique was used to select 19 Grade 10 Mathematics learners and 2 Mathematics teachers at a rural school in Eastern Cape Province. Data were collected using interviews, observations, and document reviews and these data were analysed using thematic analysis. Research findings revealed that while some factors such as evaluation methods, time limitations, and insufficient motivation may impede the optimal implementation of Guided Discovery Learning, this instructional strategy is beneficial in the cultivation of critical thinking and problem-solving abilities, which in turn enhances mathematics learners’ academic performance. Based on the findings, it was recommended that mathematics teachers should promote the utilisation of technology and multimedia resources to support learners in their visualisation and exploration of mathematical concepts in the use of GDL to enhance mathematics learners’ performance.